Deciphering Default Mode Network Dynamics in Alcohol Use Disorder Through Directed Transfer Function Analysis of EEG - Komal Masroor; Danish M. Khan; Hashim Raza Khan; Norashikin Yahya; Kamran Arshad; Khaled Assaleh (IEEE Access)
In recent years, neuroscience has focused on understanding how the human brain relates to behavior and cognition, employing advanced techniques to analyze temporal and spatial brain activity. Alcohol Use Disorder (AUD) is a significant concern, marked by compulsive alcohol consumption despite severe consequences. Effective diagnosis often relies on subjective assessments, underscoring the need for objective biomarkers. This study investigates the physiological mechanisms of alcohol’s impact on brain connectivity within the default mode network (DMN), a critical hub for cognitive and emotional processing. EEG data from 30 AUD patients (AUD-P) and 30 healthy controls (HC) revealed significant connectivity disruptions, particularly in frontal and parietal regions. Key findings include reduced connectivity between F3 and Fz and diminished frontal-parietal connections, such as F $4← $ P4 and Pz $← $ F4, linked to impaired executive functions, memory encoding, and visuospatial attention. A few regions, like Pz $← $ F3, showed increased connectivity, suggesting compensatory mechanisms. Graphical analysis confirmed widespread hypoactivation in the right hemisphere, correlating with cognitive deficits such as motor coordination issues, memory blackouts, and confabulations. These results emphasize the potential of targeting DMN connectivity using neurofeedback techniques to rehabilitate AUD patients and reduce relapse risk.